Long-term effects of adaptive customization support on elderly people - Hooshyar, Danial; Lee, Seolhwa; Yang, YeongWook; Jo, Jaechoon; Lim, Heuiseok (Cognition, technology & work, 2019)
A mixed-initiative interface conjoins aspects of both adaptable and adaptive interfaces in cases where adaptive customization assistance is added to an adaptable interface, improving the efficacy of customization, efficiency of interactions and user satisfaction. Although many studies showed the efficiency of adaptive customization support, they were either conducted within a laboratory with short-term settings or failed to consider the long-term results of the approach on the elderly. Thus, this study aims to assess the capabilities of adaptive assistance derived from the cognitive and behavioral information of users within an adaptive mixed-initiative UI/UX system (SmartSenior) designed to assist elderly people by improving their familiarity with smart devices. Drawing on cognitive and behavioral data of users, adaptive support was offered by way of customization suggestions that users could accept or disregard at their own discretion. For 10 weeks, 20 senior citizens used SmartSenior, and their actions within the interface were recorded. Half of the test subjects received support and the other half did not. The customization behavior and activity of the two groups were then compared, along with subjective responses concerning the customization support. Results demonstrated that test subjects who were supported made more effective use of SmartSenior’s customization features than those who went unsupported. Among the experimental group, subjects accepted most of the customization suggestions provided, and all of them praised the utility of the support and perceived it as beneficial. Moreover, the results show that customization support is more beneficial to users who would never customize of their own volition; such users will be increasingly likely to do so with support. In conclusion, adaptive customization support helps the elderly to more effectively customize their interface, and hence it would helpfully augment the standard adaptable UI/UX.